Genetic analysis of a signal transduction pathway : the regulation of invasive growth and starch degradation in Saccharomyces cerevisiae - Van Dyk, Dewald, 1975- (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2004.